Vegetation composition, structure and distribution status of trees used by two tropical fruit bat species in degraded habitats of Northeast India. Issue 2 (2nd April 2016) - Majumdar, Koushik; Majumder, Joydeb; Datta, B. K.
Abstract: Forest composition, structural attributes and the availability of foraging resources strongly determine the duration of roosting and survival of fruit bat species. The quantitative vegetation inventory was applied to examine the quality of two bat species' [( Cynopterus sphix (in Habitat 1) and Pteropus giganteus (in Habitat 2))] habitats in Northeast India. Five 500 × 10 m (0.5 ha) transects were laid out for each bat species to record and measure all plants with a ≥10 cm girth. The obtained results showed that the dominant plant families in the habitats studied were Fabaceae, Moraceae, Euphorbiaceae and not Myrtaceae, Moraceae, Sapotaceae as potential tropical bat-favoured plant families. We recorded six roosting, 25 foraging trees out of 110 species in Habitat 1 and 10 roosting, 27 foraging trees out of 93 species in Habitat 2. Woody plant density and the basal area significantly differed between the habitats. The arrangement of stems density-girth and density-height classes suggested that mature and upper canopy-forming trees were scarce. Most trees preferred by bats exhibited the random distribution pattern with a very low Important Value Index. Forest ecological data can be used in fruit bat conservation programmes for the resource quantification, monitoring of fruit bat habitats, management and restoration of preferred trees as well as for the protection of the remaining fragmented forests.